2011
DOI: 10.1016/j.molcel.2011.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cdk1 Substrate Specificity during the Cell Cycle

Abstract: SummaryCdk specificity is determined by the intrinsic selectivity of the active site and by substrate docking sites on the cyclin subunit. There is a long-standing debate about the relative importance of these factors in the timing of Cdk1 substrate phosphorylation. We analyzed major budding yeast cyclins (the G1/S-cyclin Cln2, S-cyclin Clb5, G2/M-cyclin Clb3, and M-cyclin Clb2) and found that the activity of Cdk1 toward the consensus motif increased gradually in the sequence Cln2-Clb5-Clb3-Clb2, in parallel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
242
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(259 citation statements)
references
References 35 publications
17
242
0
Order By: Relevance
“…One explanation for the inability of CLB1 or CLB3 to promote premeiotic DNA replication when expressed under regulation of the CLB5 promoter, even when combined with swe1 deletion, is that they may be less effective than Clb5 at interacting with substrates required for premeiotic DNA replication. While some Cdk1 substrates are effectively phosphorylated by either Clb3-Cdk1 or Clb5-Cdk1, a subset of protein substrates displays very strong preference for either Clb3 or Clb5 (Koivomagi et al 2011). Additionally, both twohybrid and proteomic screens have identified distinct arrays of interacting proteins for Clb3 and Clb5 with surprisingly little overlap (Ito et al 2001;Archambault et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation for the inability of CLB1 or CLB3 to promote premeiotic DNA replication when expressed under regulation of the CLB5 promoter, even when combined with swe1 deletion, is that they may be less effective than Clb5 at interacting with substrates required for premeiotic DNA replication. While some Cdk1 substrates are effectively phosphorylated by either Clb3-Cdk1 or Clb5-Cdk1, a subset of protein substrates displays very strong preference for either Clb3 or Clb5 (Koivomagi et al 2011). Additionally, both twohybrid and proteomic screens have identified distinct arrays of interacting proteins for Clb3 and Clb5 with surprisingly little overlap (Ito et al 2001;Archambault et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the contention that cyclins target Cdk activity to the correct substrates and hence the cyclin provides specificity to the Cdk activity (Cross et al 1999;Roberts 1999;Loog and Morgan 2005;Bhaduri and Pryciak 2011;Koivomagi et al 2011;Pagliuca et al 2011). In addition to interaction with protein substrates, the specificity of cyclins for particular functions can be imparted by the timing of accumulation, the activity of cyclin-CDK inhibitors, and by subcellular localization (Draviam et al 2001;Miller and Cross 2001;Moore et al 2003;Carlile and Amon 2008).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We recently presented a detailed study on the specificity of budding yeast cyclinCdk1 complexes and outlined the general mechanisms underlying changes in Cdk1 specificity during the cell cycle. 10 We found that the sequentially appearing cyclins gradually increase the specificity of Cdk1 toward the optimal Cdk consensus site (Fig. 1).…”
Section: Cdk1mentioning
confidence: 77%
“…6 Therefore, in addition to binding certain targets with varying affinities, cyclins also appear to be able to modulate the behavior of the cdk kinase partner toward those proteins. It will be interesting to extend these studies to human cyclins and Cdks.…”
mentioning
confidence: 99%